Unconventional superconductivity in the strong-coupling limit for the heavy fermion system CeCoIn5 - Fasano, Y.; Szabó, P.; KaÄ_x008d_marÄ_x008d_ík, J.; Pribulová, Z.; Pedrazzini, P.; Samuely, P.; Correa, V.F.; Fasano, Yanina; Correa, Víctor Félix; Pedrazzini, Pablo (Elsevier, 2018)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina